About the Calculation of Electronic Transitions in the Original CNDO/2 Treatment - Finkelstein, G.; Segre de Giambiagi, M.; Giambiagi, M. (1973)
Fil: Finkelstein, Gloria. Comisión Nacional de Energía Atómica; Argentina